Economic Management of Cooperative-Based Islamic Boarding School in North Lombok Regency - Muhammad Mahfuz (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study examines the management of Islamic boarding school economics based on cooperatives in North Lombok Regency as an effort to realize economic independence of Islamic boarding schools. The research objectives are to analyze the cooperative-based pesantren economic management model, identify the role of cooperatives in supporting pesantren economic independence, determine supporting and inhibiting factors, and assess the impact of cooperative management on students and surrounding communities. The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation. Research subjects include pesantren administrators, cooperative managers, students, and surrounding communities. The results show that the management of pesantren economy through cooperatives is carried out by implementing management functions including planning, organizing, implementing, and controlling. Pesantren cooperatives play a strategic role in providing business capital, developing productive business units, and empowering the economy of students and communities. Supporting factors include the commitment of pesantren leaders, active participation of students, and community support. While inhibiting factors include limited human resources, lack of capital, and modern management challenges. Positive impacts include improved student welfare, job creation, and strengthened economy of communities around the pesantren.